2022
DOI: 10.1155/2022/8727566
|View full text |Cite
|
Sign up to set email alerts
|

The Bioinformatical Identification of Potential Biomarkers in Heart Failure Diagnosis and Treatment

Abstract: Background. Heart failure (HF) is defined as the inability of the heart’s systolic and diastolic function to properly discharge blood flow from the veins to the heart. The goal of our research is to look into the possible mechanism that causes HF. Methods. The GSE5406 database was used for screening the differentially expressed genes (DEGs). Gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and Protein-Protein Interaction (PPI) network were applied to analyze DEGs. Besides, cell counting Kit-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…MAPK family is a kind of serine/threonine kinase, and also participates in stress reaction processes such as inflammation, cell hypertrophy, proliferation, and apoptosis. Among them, MAPK1 is a biomarker of heart failure, which is closely related to the occurrence and development of heart failure; [31] MAPK14 is involved in the process of energy metabolism related to heart failure. [32] TP53 is an important tumor suppressor gene in the human body.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK family is a kind of serine/threonine kinase, and also participates in stress reaction processes such as inflammation, cell hypertrophy, proliferation, and apoptosis. Among them, MAPK1 is a biomarker of heart failure, which is closely related to the occurrence and development of heart failure; [31] MAPK14 is involved in the process of energy metabolism related to heart failure. [32] TP53 is an important tumor suppressor gene in the human body.…”
Section: Discussionmentioning
confidence: 99%
“…The COL1A1 gene expression product is the primary component of the ECM, and research has demonstrated its myocardial protective impact on HF [ 23 ]. Additionally, it has been recognized as a potential biomarker for the advancement of HF, specifically in predicting the progression from HF diagnosis to the survival rate one year after transplantation [ 23 , 24 ]. The COL3A1 gene encodes for the synthesis of the collagen alpha-1(III) chain.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that CCND1 may serve as an underlying biomarker of idiopathic dilated cardiomyopathy [ 38 ]. In fact, idiopathic dilated cardiomyopathy is one of the most significant triggers of HF, and its histological manifestations include cardiomyocyte hypertrophy, interstitial fibrosis, and myofibril loss [ 24 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…SPCS3 belongs to the signal peptidase complex, which cleaves signal peptides from ER-targeted faulty proteins and thus maintains a healthy membrane proteome [ 53 ]. Spcs3 was reported to be differentially expressed in ischemic human and murine cardiomyopathy and in pressure-overloaded hearts [ 35 , 54 , 55 ]. Future loss- and gain-of-function studies are required to determine whether these identified candidates have a detrimental effect on the pathological remodeling and HF progression upon VO exposure or whether they are indeed protective.…”
Section: Discussionmentioning
confidence: 99%